The Globalization of Refugee Flows - Devictor, Xavier; Do, Quy-Toan; Levchenko, Andrei A. (World Bank, Washington, DC, 2020)
This paper analyzes the spatial distribution of refugees over 1987–2017 and establishes several stylized facts about refugees today compared with past decades. Refugees still predominantly reside in developing countries neighboring their country of origin. However, compared to past decades, refugees today (i) travel longer distances, (ii) are less likely to seek protection in a neighboring country, (iii) are less geographically concentrated, and (iv) are more likely to reside in a high-income OECD country. The findings bring new evidence to the debate on refugee responsibility-sharing.